Organization of Mega Events based on the FIFA World Cup in Qatar - Kacper Myler (Nicolaus Copernicus University in Toruń, 2023)
This article is the result of research conducted as part of the diploma thesis entitled "Organization of Mega Events based on the FIFA World Cup in Qatar", defended at the Nicolaus Copernicus University in Toruń in 2023. The article focuses on the issue of organizing mega events, using as a case study FIFA World Cup in Qatar. The analysis covers various aspects of managing such large sports events and identifies the benefits and threats arising from the role of the organizer of a championship tournament. Additionally, as a result original research using a survey questionnaire, participants' opinions were collected regarding the assessment of the organization of the entire event from the viewer's perspective. The main aim of the article is to present various strategies for managing championship events and to identify key aspects influencing the effective management of mega events. The first chapter is an introduction to the basic issues related to the organization of events, including the types, features and goals of these events, as well as the characteristics of mega-events. The following chapters focus on the analysis of organizational aspects and controversies related to the FIFA World Cup and discuss the advantages and disadvantages of the role of the organizer of a championship tournament, including the management of communication and technical infrastructure and fan groups. In the last chapter, research was conducted using a survey questionnaire to understand fans' impressions of FIFA World Cup Qatar 2022. The research results were described and summarized, shedding light on the overall impressions and opinions of event participants.